ANALYSIS AND DESIGN OF PROMOTIONAL ADVERTISEMENTS FOR TOKOPEDIA ELECTRONIC COMMERCE CONSUMER PURCHASES - Hamidi, Hafiz (Sean Institute, 2022)
This study evaluates Tokopedia commercial videos and asks video specialists their opinions. Eight video experts participated in this FGD-based study. The author analyzed potential and problems, collected data, and designed video tutorials in pre-production. The production staff coordinates, prepares equipment, and takes movies. Post-production comprises editing, media and language validation, and revision. The study found that informants liked Tokopedia's ads. They liked the video. The video was criticized for its sound quality and lack of useful ads, however other sources offered solutions. According to the research, the Tokopedia commercial film is good and caught the informants' interest. However, certain things need to be addressed to make the ad videos better at marketing Tokopedia items and services. This research should help corporations improve their video ads. Tokopedia's commercial film caught the informants' attention and was well-received. However, certain things need to be addressed to make the ad videos better at marketing Tokopedia items and services. This research should help corporations improve their video ads. Tokopedia's commercial film caught the informants' attention and was well-received. Tokopedia's marketing videos may be better at showcasing its products and services. Companies can use this study to improve their video ads.